Performance enhancement of a flat plate solar collector using titanium dioxide nanofluid and polyethylene glycol dispersant - Said, Z.; Sabiha, M.A.; Saidur, Rahman; Hepbasli, A.; Rahim, Nasrudin Abd; Mekhilef, Saad; Ward, T.A. (Elsevier, 2015)
The use of TiO2 water nanofluid as a working fluid for enhancing the performance of a flat plate solar collector has been studied. The volume fraction of the nanoparticles was 0.1 and 0.3 respectively, while the mass flow rates of the nanofluid varied from 0.5 to 1.5 kg/min, respectively. Thermo-physical properties and reduced sedimentation for TiO2-nanofluid was obtained using PEG 400 dispersant. The results reveal the impact and importance of each of these parameters. Energy efficiency increased by 76.6 for 0.1 volume fraction and 0.5 kg/min flow rate, whereas the highest exergy efficiency achieved was 16.9 for 0.1 volume fraction and 0.5 kg/min flow rate. Results showed that the pressure drop and pumping power of TiO2 nanofluid was very close to the base fluid for the studied volume fractions. (C) 2015 Elsevier Ltd. All rights reserved.